Pengaruh Empowerment, Self Efficacy, dan Budaya Organisasi Terhadap Kinerja Karyawan - Sri Wahyu Lelly Hana Setyanti; Marmono Singgih; Nur Azizah (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Employee performance affects the company's ongoing activities, and better employee performance will help the company develop the company for the better. Improved employee performance will bring progress for the company to survive in an unstable competitive business environment. This study aims to examine and analyze the effect of empowerment, self-efficacy, and organizational culture on PT employees' performance. Zebra Agrindo Utama Jember. The variables used are Empowerment (X1), self-efficacy (X2), corporate culture (X3), and employee performance (Y). The population in this study were employees of PT. Zebra Agrindo Utama Jember, totaling 60 employees. The sampling technique used is the saturated sample. This study uses multiple linear regression analysis with independent variables, namely empowerment, self-efficacy, and organizational culture. The dependent variable is employee performance. This study uses qualitative data quantified with primary data sources obtained through questionnaires distributed to respondents, namely employees of PT. Zebra Agrindo Utama Jember, and secondary data obtained from journals, articles, and literature related to empowerment, self-efficacy, organizational culture, and employee performance. The results showed that empowerment, self-efficacy, and corporate culture had a positive and significant effect. On the variable performance of employees of PT. Zebra Agrindo Utama Jember, so that the better the employee's perception of empowerment, self-efficacy, and organizational culture by employees, the better the employee's performance